Understanding and addressing β-lactam resistance mechanisms in gram-negative bacteria in Lebanon: A scoping review - Yara Khachab; Mohamad Hodroj; Elie Salem Sokhn (Heliyon)
Background: A growing threat to public health is the worldwide problem of antimicrobial resistance (AMR), in which gram-negative organisms are playing a significant role. Antibiotic abuse and misuse, together with inadequate monitoring and control protocols, have contributed to the emergence of resistant strains. This global scenario prepares us to look more closely at the situation in Lebanon. The aim of this review is to investigate in detail the resistance mechanisms and related genes that are displayed by gram-negative organisms in Lebanon. Methods: A comprehensive analysis was carried out to pinpoint and gather information regarding gram-negative bacteria displaying resistance to antibiotics. To contribute to a complete understanding of the current state of antibiotic resistance in gram-negative strains, it was intended to collect and evaluate data on these organisms' resistance patterns in a comprehensive manner. Results: Several studies have emphasized the prevalence of carbapenem-resistant Enterobacteriaceae (CRE) in Lebanon, specifically noting Escherichia coli and Klebsiella pneumoniae as the most frequent culprits, with OXA-48 and NDM-1 being the primary carbapenemases discovered. Furthermore, the TEM β-lactamase families are the primary source of extended-spectrum β-lactamases (ESBLs) in Shigella and Salmonella. Additionally, resistant strains of Acinetobacter baumannii and Pseudomonas aeruginosa have been linked to nosocomial infections in the country. Conclusion: There is a considerable frequency of antibiotic overuse and misuse in Lebanon, based to the limited data available on antibiotic consumption. In conclusion, antibiotic stewardship initiatives and additional research beyond the confines of single-center studies in Lebanon are needed.